THE IMPACT OF DESIGN THINKING-BASED LEARNING ACTIVITIES IN THE CONTEXT OF MENTOR TEACHER SUPERVISION ON THE DESIGN THINKING MINDSET OF PRESERVICE SCIENCE TEACHERS - Ramsri, Sarawut; Samiphak, Sara (Journal of Educational Review Faculty of Education in MCU, 2025)
This research aimed to (1) develop the design thinking mindset of preservice science teachers through design thinking-based learning activities within a mentoring context, and (2) compare the levels of their design thinking mindset before and after implementing these activities. The target group consisted of four fourth-year preservice teachers majoring in general science who were undertaking their teaching practicum at secondary schools. The research instruments included a set of learning activities based on the design thinking process and a design thinking mindset assessment. Data were analyzed using descriptive statistics and relative gain scores (G Scores). The findings revealed that: 1) The design thinking-based learning activities, conducted under the supervision of mentor teachers, effectively enhanced the preservice science teachers’ design thinking mindset. This was particularly evident in the dimensions of belief in collaboration and optimism, both of which reached their full potential. 2) The preservice science teachers’ design thinking mindset after participating in the activities was higher than before across all dimensions, with a G Score of 1.0, indicating full potential development.